The Rational qKZ Equation and Shifted Non-Symmetric Jack Polynomials - Kakei, S.; Nishizawa, M.; Saito, Y.; Takeyama, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We construct special solutions to the rational quantum Knizhnik-Zamolodchikov equation associated with the Lie algebra glN. The main ingredient is a special class of the shifted non-symmetric Jack polynomials. It may be regarded as a shifted version of the singular polynomials studied by Dunkl. We prove that our solutions contain those obtained as a scaling limit of matrix elements of the vertex operators of level one.